2017
DOI: 10.1016/j.ydbio.2017.07.013
|View full text |Cite
|
Sign up to set email alerts
|

bHLH proneural genes as cell fate determinants of entero-endocrine cells, an evolutionarily conserved lineage sharing a common root with sensory neurons

Abstract: Entero-endocrine cells involved in the regulation of digestive function form a large and diverse cell population within the intestinal epithelium of all animals. Together with absorptive enterocytes and secretory gland cells, entero-endocrine cells are generated by the embryonic endoderm and, in the mature animal, from a pool of endoderm derived, self-renewing stem cells. Entero-endocrine cells share many structural/functional and developmental properties with sensory neurons, which hints at the possibility of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 113 publications
(159 reference statements)
2
22
0
Order By: Relevance
“…At least 95% of them express peptide hormones, often more than one and with regional stereotypy ( Veenstra et al 2008 ; Veenstra 2009 ; Reiher et al 2011 ; Beehler-Evans and Micchelli 2015 ). The developmental program of EE cells shares similarities with that of neurons, probably reflecting a common phylogenetic origin ( Hartenstein 2006 ; Hartenstein et al 2010 , 2017 ). Consistent with this idea, all known EE peptide hormones (possibly with the exception of one of the insect CCHamides; S. Li et al 2013 ) are also produced by the brain.…”
Section: Functionsmentioning
confidence: 90%
“…At least 95% of them express peptide hormones, often more than one and with regional stereotypy ( Veenstra et al 2008 ; Veenstra 2009 ; Reiher et al 2011 ; Beehler-Evans and Micchelli 2015 ). The developmental program of EE cells shares similarities with that of neurons, probably reflecting a common phylogenetic origin ( Hartenstein 2006 ; Hartenstein et al 2010 , 2017 ). Consistent with this idea, all known EE peptide hormones (possibly with the exception of one of the insect CCHamides; S. Li et al 2013 ) are also produced by the brain.…”
Section: Functionsmentioning
confidence: 90%
“…Nonetheless, like other sensory epithelial cells of endodermal origin, enteroendocrine cells have prominent neuronal features. They are electrically excitable (Rogers et al, 2011 ), form synapses (Bohórquez et al, 2015 ), and release neuropeptides and neurotransmitters in response to stimuli (Hartenstein et al, 2017 ). Because of the mounting evidence that these cells act as true epithelial transducers, further exploration will elucidate the precise origin of these cells.…”
Section: The First Enteroendocrine Cellmentioning
confidence: 99%
“…The first enteroendocrine cells appear early in gestation, during gut tube development. At this point the cells remain mitotically active (Crosnier, 2005 ; Penkova et al, 2010 ; Hartenstein et al, 2017 ). Upon folding of the gut epithelium into crypts and villi, most cells are differentiated, and further proliferation occurs from the Lgr5-expressing adult stem cells of the crypts (Barker et al, 2007 ).…”
Section: The First Enteroendocrine Cellmentioning
confidence: 99%
“…However, endoderm-derived cells, which contain neurotransmitters and hormones, are categorized as enteroendocrine cells in vertebrate digestive tracts (3,49). Some enteroendocrine cells have axon-like processes, which are shorter than neuronal axons, and target the gut lumen and enteric neurons on the basal side of the gut wall (49,50). It is also reported that hormones released from enteroendocrine cells regulate the contraction and relaxation of the pyloric sphincter (51).…”
Section: Discussionmentioning
confidence: 99%
“…Because sEN in sea urchin larvae shares some of these morphological and functional characteristics, we cannot conclude that SynBpositive cells are neurons or enteroendocrine cells. It has been suggested that peripheral sensory neurons and enteroendocrine cells share common origins (50), which makes the difference indistinct. Although we are unable to fully distinguish the nature of these cells, sea urchin nNOS-positive endoderm-derived cells suggests an evolutionary history in which the common deuterostome ancestor had endodermally derived cells that regulated gut function.…”
Section: Discussionmentioning
confidence: 99%